Optical ph sensing material prepared from doped sol-gel film for use in acid-base titration - Musa Ahmad; T.W. Tan (ASEAN Journal on Science and Technology for Development, 2001)
An optical pH sensing material has been prepared in this study by using sol-gel technique. Bromothymol blue, bromophenol blue and thymol blue were chosen in this study as acidbase indicators for strong acid-strong base, strong acid-weak base and weak acid-strong base titration, respectively. The results show that these indicators could be successfully entrapped inside the sol-gel film and still maintain its chemical behaviour as in solution. The entrapped acid-base indicators respond well to any pH changes and could be used to determine the end-point of the acid-base titration.